Epstein-Barr virus: the mastermind of immune chaos - Silva, Jean de Melo; Alves, Carlos Eduardo de Castro; Pontes, Gemilson Soares (Frontiers in Immunology, 2024)
The Epstein-Barr virus (EBV) is a ubiquitous human pathogen linked to various diseases, including infectious mononucleosis and multiple types of cancer. To control and eliminate EBV, the host's immune system deploys its most potent defenses, including pattern recognition receptors, Natural Killer cells, CD8 + and CD4 + T cells, among others. The interaction between EBV and the human immune system is complex and multifaceted. EBV employs a variety of strategies to evade detection and elimination by both the innate and adaptive immune systems. This demonstrates EBV's mastery of navigating the complexities of the immunological landscape. Further investigation into these complex mechanisms is imperative to advance the development of enhanced therapeutic approaches with heightened efficacy. This review provides a comprehensive overview of various mechanisms known to date, employed by the EBV to elude the immune response, while establishing enduring latent infections or instigate its lytic replication.